A Literature Review on Environmental Literacy Among Senior High School Students in Indonesia - Maimunah Ritonga; Ayu Andini; Arif Bulan (Jurnal Ilmiah Literasi Indonesia, 2025)
Environmental literacy has become an essential competency that senior high school students in Indonesia must possess to address sustainability challenges. This literature review aims to map the development of research on environmental literacy among high school students, including conceptual definitions, theoretical frameworks used, literacy levels based on empirical findings, and commonly applied assessment instruments. The results indicate that environmental literacy at the high school level generally falls into the moderate category, with students demonstrating relatively good basic environmental knowledge but lacking strong cognitive skills and pro-environmental behaviors. Previous studies also reveal that curriculum factors, school facilities, teacher pedagogy, family support, and exposure to digital media significantly influence the development of environmental literacy. The most widely used instruments include the MSELS, Environmental Attitude Scale (EAS), New Ecological Paradigm (NEP), as well as locally developed ESD-based questionnaires adapted to the Indonesian context. This review highlights the need for integrating Education for Sustainable Development (ESD) approaches, strengthening project-based pedagogy, and improving green school facilities to promote more comprehensive and action-oriented environmental literacy.